Regenerative-Relational Tritangtu: Sundanese Triadic Transformation Model - Wanda Listiani; Heddy Shri Ahimsa-Putra; GR LonoLastoroSimatupang; Yasraf Amir Piliang Amir Piliang (LP2M ISBI Bandung, 2013)
ABSTRACT Tritangtu or Trinity mindset is a Sundanese and Minang community cosmology that consists of three entities (three patterns). Tritangtu as the local wisdom is also underlying the creative actors mental structure on making their works either in the form of performance, artifacts philosophy value, or in other cultural products in Indonesian community. This study used ethnographic method with data collection techniques were participant observation in-depth interviews and documentation. The object of study is the creative actors practice at the design field in Bandung.The result of study pointed out the Sundanese Tritangtu transformation from the permanent struc- ture to dynamic structure. The change in the structure is determined by the relation between the de- sign elements forming structure with the global market segmentation. Lending Sundanese identity markers, especially the folk culture or the past traditions is regenerative efforts to harmonize the three patterns in encountering and winning the free-market competition in Indonesia. Keyword: Tritangtu, Sundanese Triadic Transformation ModelAbstrak Tritangtu atau pola pikir tritunggal merupakan kosmologi masyarakat Sunda dan Minang yang terdiri dari tiga entitas (pola tiga). Tritangtu sebagai kearifan lokal juga melatarbelakangi struktur mental pelaku kreatif dalam membuat karya baik berupa pertunjukan, nilai filosofi artefak mau- pun produk budaya lainnya di masyarakat Indonesia. Penelitian ini menggunakan metode etnografi dengan teknik pengumpulan data observasi partisipasi, wawancara mendalam dan dokumentasi. Obyek penelitian ini adalah praktik pelaku kreatif di bidang desain di Bandung. Hasil penelitian ini menunjukkan adanya transformasi tritangtu Sunda dari struktur yang tetap menjadi struktur dinamis. Perubahan struktur ini ditentukan oleh relasi antar struktur pembentuk unsur desain de- ngan segmentasi pasar global. Peminjaman penanda identitas Sunda khususnya budaya rakyat atau tradisi masa lalu merupakan upaya regeneratif dalam usahanya untuk harmonisasi pola tiga dalam menghadapi dan memenangkan persaingan pasar bebas di Indonesia. Kata kunci : Tritangtu, Model Transformasi Triadic Sunda